What Has Been Discussed on Zakat Institutions? A Bibliometric Study - Andriani Andriani; Eko Ganis Sukoharsono; Wuryan Andayani; Roekhudin Roekhudin (Journal of Islamic Monetary Economics and Finance, 2025)
This study conducts a comprehensive bibliometric analysis of research on zakat published between 2011-2024 with the aims to map its intellectual structure, thematic evolution, and collaboration networks. Using science mapping principles, 312 documents from Scopus database are analyzed through co-authorship, citation counts, co-occurrence patterns, thematic analysis, and network visualization using R-based bibliometrix package and biblioshiny interface with AI-assisted visualization. Results reveal five distinct thematic clusters: social and psychological aspects of zakat compliance; digital transformation and technology adoption; institutional efficiency with Malaysian focus; financial governance and accountability; and macro-level zakat management in Indonesia. The field demonstrates remarkable growth with a 28.29% annual growth rate, dominated by Malaysian and Indonesian institutions accounting for over 65% of publications. Research evolution shows a progression from foundational governance issues (2011-2016) to strategic management (2016-2020) and contemporary digital innovation (2020-2024). The study identifies significant research gaps, particularly the absence of in-depth qualitative methodologies and limited cross-country comparative studies. This study offers novel insights into the evolution of zakat governance and highlights the need for interdisciplinary and cross-regional research to strengthen institutional relevance and inclusivity in zakat management. Acknowledgment The authors received the support funding for research, authorship and publication of this article from The Indonesian Education Scholarship (Beasiswa Pendidikan Indonesia), Center for Higher Education Funding and Assessment (Pusat Pelayanan Pembiayaan dan Asesmen Pendidkan Tinggi), Ministry of Higher Education, Science, and Technology of Republic Indonesia, and Endowment Fund for Education Agency (Lembaga Pengelola Dana Pendidikan). The authors gratefully acknowledge the support and facilities provided by UPT Perpustakaan Universitas Brawijaya in the completion of this article.